Development and evaluation of a bladder Cancer specific survivorship care plan by patients and clinical care providers: a multi-methods approach - Cheryl T. Lee; Nihal E. Mohamed; Sailaja Pisipati; Qainat N. Shah; Piyush K. Agarwal; Tracy M. Downs; Michael Droller; Scott M. Gilbert; Heather H. Goltz; Simon J. Hall; Mohamed Hendawi; Jean Hoffman-Censits; et al. (BMC, 2020)
Abstract Background, context and purpose In spite of the mixed evidence for their impact, survivorship Care Plans (SCPs) are recommended to enhance quality of care for cancer survivors. Data on the feasibility of SCPs in bladder cancer (BC) is sparse. Using a mixed-methods approach, this study describes the iterative development, acceptability and feasibility of BC specific SCP (BC-SCP) in clinical settings. Methods In Phase I, we developed the BC-SCP. In Phase II, we conducted four focus groups with 19 patients and 15 providers to examine its acceptability and usability challenges. Data analyses using the Atlas.ti program, informed refinement of the BC-SCP. In Phase III, we conducted feasibility testing of the refined BC-SCP with 18 providers from 12 health-centers. An encounter survey was completed after each assessment to examine the feasibility of the BC-SCP. Chi-square and Fisher Exact tests were used for comparative analyses. Results During phase I, we observed high patient and provider acceptability of the BC-SCP and substantial engagement in improving its content, design, and structure. In Phase II, providers completed 59 BC-SCPs. Mean time for BC-SCP completion was 12.3 min. Providers reported that BC-SCP content was clear, did not hamper clinic flow and was readily completed with easy-to-access information. Comparative analyses to examine differences in SCP completion time by patient clinico-demographic characteristics and provider type revealed no significant differences. Conclusions Our BC-SCP has clinical relevance, and can be used in an active practice setting. However, considerable progress will be necessary to achieve implementation of and sharing the BC-SCP with patients and care providers, particularly within the electronic medical record. In summary, BC-SCPs are essential to improve the follow up care of BC survivors. Clinical resources are required to ensure appropriate implementation of BC-SCPs. Trial registration Study HUM00056082.